2009
DOI: 10.2220/biomedres.30.53
|View full text |Cite
|
Sign up to set email alerts
|

Stromal laminin-5γ2 chain expression is associated with the wall-invasion pattern of gallbladder adenocarcinoma

Abstract: Our previous study demonstrated that the pT2 and pT3-4 gallbladder carcinomas can be classified into two groups, i.e. infiltrative growth type (IG type) and destructive growth type (DG type) and that the DG type is associated with poor differentiation, aggressive infiltration, and decreased postoperative survival. The present study focused on the clinicopathologic significance of laminin-5γ2 chain expression as an indicator of local aggressiveness and Ki-67 labeling index (Ki-67 LI) as an indicator of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…The low molecular weight protein groups are 40 to 54 kD: CK7, 8, 17-20, and the high molecular weight protein groups are 48 to 67 kD: CK1-6, 9-16 (3). metastases; M1, distant metastases (22 (18). In each patient, one representative histological specimen at the deepest invaded area of the esophageal cancer lesion was selected for immunohistochemistry.…”
mentioning
confidence: 99%
“…The low molecular weight protein groups are 40 to 54 kD: CK7, 8, 17-20, and the high molecular weight protein groups are 48 to 67 kD: CK1-6, 9-16 (3). metastases; M1, distant metastases (22 (18). In each patient, one representative histological specimen at the deepest invaded area of the esophageal cancer lesion was selected for immunohistochemistry.…”
mentioning
confidence: 99%
“…Lymph node metastasis is the most crucial parameter for predicting survival (16,29,35). The spread of cancer cells via the lymphatic system to regional lymph nodes is an important early event INFc; and INFc, the tumor showing scirrhous growth and an indistinct border with the surrounding tissue (21). In each patient, one representative histological specimen at the deepest invaded area of an esophageal cancer lesion was selected for immunohistochemistry.…”
mentioning
confidence: 99%
“…Mucin is a heterogeneous group of high molecular weight glycoproteins with many carbohydrate side chains. The mucin shares the common features of having an extensive tandem repeat region, and a peptide domain containing a high per- logical differentiation, lymphatic invasion, venous invasion, lymph node status, neural invasion, and mode of subserosal infiltration (18)(19)(20). In present study, both histological phenotype and MUCs expression were significantly correlated with wall-invasion pattern of GBC.…”
Section: Histological Phenotype and Clinicopathological Factors Of Gbcmentioning
confidence: 99%
“…Several previous studies have demonstrated high risks of disease progression, using surgically-resected GBC cases, and histological grade, depth of wall infiltration, and lymph node status have been determined to be clinicopathological prognostic factors (6,22). In addition, we have classified the wall-invasion pattern of GBC into two groups, i.e., infiltrative growth type (IG type) and destructive growth type (DG type) (18)(19)(20). The DG type was significantly associated with lymph node metastasis and poor prognosis.…”
mentioning
confidence: 99%